The Effect of Schinus terebinthifolius Raddi (Anacardiaceae) Bark Extract on Histamine-Induced Paw Edema and Ileum Smooth Muscle Contraction - Nunes-Neto, Paulo Alexandre; Peixoto-Sobrinho, Tadeu José Da Silva; Da Silva Júnior, Edilson Dantas; Leopoldina Da Silva, Jamilka; Rodrigo Da Silva Oliveira, Alisson; Pupo, André Sampaio [UNESP]; Araújo, Alice Valencą; Costa-Silva, Joaõ Henrique Da; Wanderley, Almir Goncąlves (Wiley, 2017)
Schinus terebinthifolius Raddi (Anacardiaceae), popularly known as red aroeira, is used in traditional medicine to treat inflammatory, gastric, and respiratory disorders. The aim of this study was to evaluate the antihistaminic activity of S. terebinthifolius (St) bark extract by using in vivo and in vitro experimental models. The effects of St were investigated on contractions induced by histamine, carbachol, and potassium chloride in isolated Guinea pig ileum. St was also studied in response to hind paw edema induced by histamine in rats. Experiments revealed that although St (250, 500, and 1,000 μg/mL) reduced the histamine-induced contractions by 9.1±1.8, 50.2±2.0, and 68.9±2.0%, respectively, it did not inhibit contractions induced by carbachol or KCl. The association of St (250 and 500 μg/mL) with hydroxyzine, an H1-antihistamine (0.125 and 0.250 μM), increased the inhibitory effect to 67.0±3.2 and 85.1±2.1%, respectively. Moreover, St (100, 200, and 400 mg/kg) decreased paw edema from its peak by 33.9, 48.4, and 54.8%, respectively, whereas hydroxyzine (70 mg/kg) inhibited the peak edema by 56.5%. Altogether, the results suggest that the bark extract of S. terebinthifolius has an antihistaminic effect (H1).